Fixação biológica de nitrogênio e FMAS no desenvolvimento da soja em solo contaminado com cobre - Andreola, Daiane Sartori (2021)
The intense and continuous use of heavy metals by anthropic activityhas increased the contamination of the soil with copper, becoming a problem that negatively affects the growth and productivity of plants and microorganisms. This work aimed to determine the influence of nitrogen-fixing bacteria and mycorrhizal fungi on the development of soybean cultivated in soil contaminated with copper. To meet this objective, three experiments were carried out: at first the nitrogen-fixing bacteria were evaluated in the development of soybeans in soil contaminated with copper; at second it were evaluated the arbuscular mycorrhizal fungi in growth, tolerance and copper accumulation in glycine max L. plants grown in soils contaminated with copper and at third, the co-inoculation was carried out between nitrogen-fixing bacteria and arbuscular mycorrhizal fungi in growth and copper accumulation in Glycine max L. The results showed that the soybean culture is negatively influenced by the addition of copper in the soil. The addition of copper in the soil has a positive interaction with the increase of this metal in the soybean grain, so areas contaminated with copper can be considered unsuitable for the cultivation of this specie. The inoculation of soybean seeds with Bradyrhizobium japonicum provides increases in the physiological characteristics of the plants and the inoculation with arbuscular mycorrhizal fungi increases the final productivity of the culture. Coinoculation decreases the effects of copper in the soil, improving the development of Glycine max L. plants.